The role of electrostatics in colicin nuclease domain translocation into bacterial cells. - Walker, D; Mosbahi, K; Vankemmelbeke, M; James, R; Kleanthous, K (2007)
The mechanism(s) by which nuclease colicins translocate distinct cytotoxic enzymes (DNases, rRNases, and tRNases) to the cytoplasm of Escherichia coli is unknown. Previous in vitro investigations on isolated colicin nuclease domains have shown that they have a strong propensity to associate with anionic phospholipid vesicles, implying that electrostatic interactions with biological membranes play a role in their import. In the present work we set out to test this hypothesis in vivo. We show that cell killing by the DNase toxin colicin E9 of E. coli HDL11, a strain in which the level of anionic phospholipid and hence inner membrane charge is regulated by isopropyl beta-D-thiogalactopyranoside induction, is critically dependent on the level of inducer, whereas this is not the case for pore-forming colicins that take the same basic route into the periplasm. Moreover, there is a strong correlation between the level and rate of HDL11 cell killing and the net positive charge on a colicin DNase, with similar effects seen for wild type E. coli cells, data that are consistent with a direct, electrostatically mediated interaction between colicin nucleases and the bacterial inner membrane. We next sought to identify how membrane-associated colicin nucleases might be translocated into the cell. We show that neither the Sec or Tat systems are involved in nuclease colicin uptake but that nuclease colicin toxicity is instead dependent on functional FtsH, an inner membrane AAA(+) ATPase and protease that dislocates misfolded membrane proteins to the cytoplasm for destruction.